A Safe Place: Jane Austen and the Richardsonian Inheritance - Fawcett, Nancy R. (My University, 1987)
Jane Austen's novels have often been viewed as realistic portrayals of the time in which she lived. This paper attempts to modify this view by examining her work in the context of the novels of Samuel Richardson, the writer whom she reportedly admired above all others. There are many differences between the two authors, but their subject matter is essentially the same: the hearts and minds of marriageable young women. Richardson's heroines, however, are threatened and harassed while Austen's are free to experience without fear, and to learn without danger. In "Sir Charles Grandison or The Happy Man", a parody she wrote of Richardson's Sir Charles Grandison, Austen satirizes Richardson's timorous heroines and aggressive heroes; in her novels, women are self-assured and men are not frightening. An examination of the social history of the eighteenth ce ntu ry and the letters of Jane Austen, however, demonstrates that the world of her novels is not the one she knew. Her much misunderstood letters, in particular, show that her attitudes towards sexual relationships have much in common with those of Samuel Richardson. In addition, her letters illustrate the source and significance of her celebrated irony. Finally, this study concentrates on Mansfield Park, the novel that appears to contradict Austen's other novels. Mansfield Park is didactic and unironic; it has an oppressed heroine, powerful male characters, and a society that neither appreciates nor defends women. In Mansfield Park the Richardsonian inheritance and Austen's social and sexual views come together and provide insights into her work. Jane Austen's heroines, with the exception of Fanny Price, inhabit a safe place she creates for them. Her rejection of the dangers of women's lives, which Richardson depicts so well, is proof, not of her realism, but of her artistry.
Keywords: Jane Austen; A Safe Place